Proceso de Selección del Personal del Gobierno Autónomo Descentralizado Municipal del Cantón Vinces - Dinora Mileidy Santillan valencia, Dinora Mileidy Santillan valencia (2017)
The Municipality of Canton Vinces Province of Los Ríos building located in the streets between Sucre and Balzar. From the year 1878 being one of the oldest buildings inside the Canton Vinces. In the mandate of Ec. Cristian Villasagua Santana, whose mission for the Vincentian population is to carry out the "execution and control of plans for the provision of public services, construction of public works, mobility, promotion of productive activities and environmental management, which participatory and inclusive approach, promote economic, social, environmental and cultural well-being "(VINCES, GAD MUNICIPAL DEL CANTON VINCES, 2014)